Logistic kinetic model for dichlorinated polyaromatic hydrocarbons (PAHs) activity in cancer signaling - Putz Ana-Maria; Putz Mihai V.; International Symposium on Analytical and Environmental Problems (17.) (2011) (Szeged) Szeged 2011. szeptember 19. (SZAB Szeged, 2012)
The logistic kinetics model of quantitative structure-activity relationships was here implemented for modeling the depletion of the CIPAHs in MCF-7 cells; it was found that the best statistical performances are given by polarizability, electronegativity and hydrophobicity within density functional framework, through a mono-linear Spectra-SAR analysis.
Keywords: Természettudományok; Kémiai tudományok